Front Cover: Balancing Histone Deacetylase (HDAC) Inhibition and Drug‐likeness: Biological and Physicochemical Evaluation of Class I Selective HDAC Inhibitors (ChemMedChem 9/2022). (5th May 2022) - Schäker‐Hübner, Linda; Haschemi, Reza; Büch, Thomas; Kraft, Fabian B.; Brumme, Birke; Schöler, Andrea; Jenke, Robert; Meiler, Jens; Aigner, Achim; Bendas, Gerd; Hansen, Finn K.
Abstract : The Front Cover shows the development of a potent and selective histone deacetylase 1 and 2 (HDAC1 and 2) inhibitor that was tailor‐made to engage the characteristic "foot‐pocket" present in both isoforms. This was achieved by a modular approach aiming to find the perfect balance between selectivity and drug‐likeliness through systematic screening and thorough biological evaluation. Cover design by Dr. Christoph Selg. More information can be found in the Research Article by Linda Schäker‐Hübner, Finn K. Hansen et al.